KAM tori for reversible partial differential equations - Zhang, Jing; Gao, Meina; Yuan, Xiaoping (Nonlinearity, 2011)
In this paper, we establish a KAM theorem for an infinite dimensional reversible system with unbounded perturbation, by which we obtain quasi-periodic solutions of a class of nonlinear Schodinger equations with a derivative in nonlinear terms, subject to Dirichlet boundary conditions.